Application of Stereoscopic Head-Mounted Displays and Interactive Virtual Reality Environments to an "Optical Illusion" Misstep and Fall Case. (November 2019) - Jacinto, Rosemarie Figueroa; Sproule, David; Williams, Jacob; Perlmutter, Sam; Arndt, Steve; Rundell, Steve
The ability to accurately depict the scene of an incident to a jury, who will never be able to experience it first-hand, is a key element of presenting trial demonstratives. In many cases, where visual perception and situational awareness are a key element in understanding the nature of an incident, traditional modes of presentation, such as two-dimensional photographs, may be insufficient and require a more sophisticated methodology. Specifically, as stereoscopic head-mounted displays (HMDs) and virtual reality (VR) programming continues to advance, it provides jurors the opportunity to experience an interactive, and more representative, virtual environment. Further, while immersed in these environments, jurors can direct their gaze to areas of interest, view them from multiple angles, and dictate the pace in which they do so providing an experience tailored to the individual that more fully utilizes the capabilities of their sensory system. Thus, forensic accident investigators, such as human factors expert witnesses, have the opportunity to leverage this technology to demonstrate aspects of perception and human performance. This study discusses the application of HMDs and VR to a real-world incident investigation, and discusses the reasons why such technology is required to accurately depict changes in walking surface level elevations.